Role of Key Factors for Biogas Development: A Case of Nepal - Yadav, Maheshwar Prasad (Economic Journal of Nepal, 2014)
of Nepal. The variables are introduced via an extension of the econometric model, whichexplicitly includes Almon (1965) Polynomial Lag Model by using SPSS. The number ofbiogas plants consists of as dependent variable for the indicator of biogas development whilenumbers of biogas plants constructed with loan, micro credit, subsidy and number of Biogascompanies have been comprised as independent variables. The empirical results have beenestimated by using annual data for the period of Fiscal Year 1992/93 to 2010/11 with entirestudy period divided into different sub-periods. The study reveals that the number of plantsconstructed with loan, micro credit, subsidy and number of Biogas companies havesignificant impact on biogas development. The study reveals the biogas development isinfluenced not only by the current values of number of plants constructed with loan, microcredit, subsidy and number of biogas companies but also by past values. The study alsoshow that subsidy and number of biogas companies play a very strong role in the biogasdevelopment while the number of plants constructed with loan and micro credit, play a weakrole in promotion of biogas in Nepal. The Economic Journal of Nepal, Vol. 34, No. 4, October-December 2011 (Issue N0. 136)